The evaluation of Sesbania sesban var nubica and Sesbania goetzei in a semi-arid environment in eastern Kenya - Nzioka, S.M.; Minin, L.K.; Dzowela, B.H. (International Livestock Centre for Africa, 1993)
Results of the performance of Sesbania growth, biomass production and pest incidence in 72 accessions of Sesbania species fertilised with phosphorus in a semi-arid environment in Eastern Kenya are presented. Sesbania sesban (L) merr var nubica had higher stem diameters, plant heights, number of branches and biomass yields than Sesbania goetzei. It also exhibited a higher coppicing ability four and eight weeks after cutting. A large variability was shown by the species especially with respect to plant height and numbers of branches, suggesting the possible use of these parameters for improvement by selection. Sesbania goetzei accessions showed better resistance to pest infestation compared to Sesbania sesban accessions. However, no clear-cut differences was found between species in their response to phosphorus fertilisation.